2017
DOI: 10.1007/s11356-017-0636-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multilayer substrate configuration in horizontal subsurface flow constructed wetlands: assessment of treatment performance, biofilm development, and solids accumulation

Abstract: This study investigates the influence of multilayer substrate configuration in horizontal subsurface flow constructed wetlands (HSCWs) on their treatment performance, biofilm development, and solids accumulation. Three pilot-scale HSCWs were built to treat campus sewage and have been operational for 3 years. The HSCWs included monolayer (CW1), three-layer (CW3), and six-layer (CW6) substrate configurations with hydraulic conductivity of the substrate increasing from the surface to bottom in the multilayer CWs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
0
9
0
4
Order By: Relevance
“…It is worth describing that microbial degradation is an important pathway during removal of pollutants in CWs. Some authors [14,16,38] have revealed that the microbial activity and metabolic richness in the interstitial water and biofilm in CWs are influenced by CW design, vegetation, and filter material. In this study, the microbial film was not analyzed, but it is recommended to analyze it along with design parameters.…”
Section: Concentration and Removal Of Pollutants In Cw Microcosmsmentioning
confidence: 99%
“…It is worth describing that microbial degradation is an important pathway during removal of pollutants in CWs. Some authors [14,16,38] have revealed that the microbial activity and metabolic richness in the interstitial water and biofilm in CWs are influenced by CW design, vegetation, and filter material. In this study, the microbial film was not analyzed, but it is recommended to analyze it along with design parameters.…”
Section: Concentration and Removal Of Pollutants In Cw Microcosmsmentioning
confidence: 99%
“…For example, sulfatoreduction implies metallic sulphides generation and subsequently its precipitated into the CW by chemical speciation. This process, in turn, results in clogging which is one of the disadvantages of CW [92][93][94][95].…”
Section: Genusmentioning
confidence: 99%
“…Parameter atau ukuran yang dapat menggambarkan kemampuan tanah dalam melewatkan air disebut sebagai konduktivitas hidrolik (Hydraulic Conductivity) (1,2,(62)(63)(64)(65)(66)(67)(68)(69)(70)(71) . Tingkat kemampuan dari tanah untuk melewatkan air sangat sekali dipengaruhi oleh kadar air di dalam tanah.…”
Section: Konduktivitas Hidrolikunclassified
“…dimana: Ks adalah konduktivitas hidrolik (1,2,(62)(63)(64)(65)(66)(67)(68)(69)(70)(71) dalam keadaan jenuh; V adalah volume air yang mengalir melalui masa (contoh) tanah dengan luas penampang A dalam jangka waktu t; dan (H2-H1) adalah perbedaan tinggi permukaan air (hydraulic head diference) yang mengalir melewati contoh (kolom) tanah sepanjang L. H1 adalah tinggi hidrolik pada titik masuknya air, sedangkan H2 adalah tinggi hidrolik pada tempat keluarnya air.…”
Section: Konduktivitas Hidrolikunclassified